Aplikasi Teori Offensive Realism Dalam Menjelaskan China Yang Memperkuat Kekuatan Ruang Angkasa Tahun 2021 - Cyril Noor Mohammad Harahap (Riviera Publishing, 2025)
This study explains that space has become a new domain in the struggle for influence of countries in international relations. Countries have the goal of securing their interests in space for political, economic and military purposes. China is one of the countries that has political interests such as space exploration by launching the first human mission in space in 2003. In its development, China created an exploration program by developing space-based military technology such as the Anti-Satellite (ASAT) counterspace weapon which was launched in 2007. China also formed the PLA Strategic Support Forces space force for the purpose of operating space control. Military policy was never clearly stated in China's space white paper in 2006 and 2011 because their goal was only for peaceful exploration. In 2016 and 2021, the statements in the space white paper had significantly different goals and explicitly led to military activities, namely to form a space force. Based on the explanation above, this study raises the question: Why is China Strengthening Space Power in 2021? The analysis of this study uses the Offensive Realism theory. This study uses a qualitative research method. Data collection techniques are sourced from secondary data sources obtained from journals, books, official documents, official statements and reports.